If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4+8x+23=3
We simplify the equation to the form, which is simple to understand
-4+8x+23=3
We move all terms containing x to the left and all other terms to the right.
+8x=+3+4-23
We simplify left and right side of the equation.
+8x=-16
We divide both sides of the equation by 8 to get x.
x=-2
| -6(r-7)=90 | | 17+2.6=30 | | 1(3/4)/4(1/8)= | | 6.9+8p=-12.3 | | 3t/4-6=t/12 | | .66(m-8)=4 | | 26m=55 | | 5t+5.7=9.2 | | 55=26m | | -6.4=x+4.3 | | 6x+3y=-30 | | r/3-r/6=2 | | -5=-4x+2x+13 | | 3(3+4)-2x-5-7x=20 | | -6-7x=8 | | -m=-8 | | x+28=-2x^2 | | -6-7=8 | | 41-5x=13x+15 | | 4n+12=2n+30 | | 6m+8=50 | | -4x+y=28 | | -4x+y= | | 6m+8=70 | | 4w-7.5=2.7 | | e+(-17)=32 | | -5(-3x-7)+6x=-91 | | 32x^3+96x^2-18x-54=0 | | 6m-7k=98 | | 9+4(x+1)=-5 | | 4(3x+1)+5(x-3)= | | 166-6x=5x+12 |